Sharia Marketing in Business: Paradigm, Ethics and Implementation of Islamic Principles - Hidayat, Chaerul; Rini Ariza; Aan Fadillah; Muhammad Reza; Amali (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Marketing is the main focus for companies in their efforts to develop and maintain their business. This article reviews in detail the concept of marketing in a general context and sharia marketing. Sharia marketing emphasizes Islamic moral principles such as faith, khalifah, balance, and justice, which form the basis for the strategy, tactics, values, and image of Islamic marketing. In addition, in practice, Islamic marketing also includes aspects of spirituality, considering competition as a partner to spur creativity. Specific characteristics of Islamic marketing include unity, faith, balance, justice, freedom of will, and benevolence. Islamic marketing ethics emphasize integrity, honesty, and good service. It is hoped that by applying these principles, companies can create a healthy business environment and provide benefits for all parties involved